O efeito da estrutura na performance dos grupos empresariais - Gama, Marina Amado Bahia (2017)
This research deals with the effect of structure on performance at the level of the business group. There are already some studies that show that size affects group performance and diversification affects this relationship negatively. However, there is a lack of more detailed evidence on how size and diversification in the complex structure of the business group affect performance at the group level. In this sense, we intend to contribute with the perspective on business groups using economic perspective and indicate under what conditions of structure business groups develop superior performance related to both size and diversification of groups. The method used was multiple regressions with panel data (2001-2013) and the fixed effect, considering a sample of 127 groups and 1.012 observations. Empirical analysis suggests that the size of business groups positively affects performance at the group level. When there are a greater number of affiliated firms closer to the holding company, there is a positive effect on performance. Otherwise, the effect tends to be negative. Yet, through the interaction between size and structure we verified that when the structure has more affiliated firms closer to the holding company, it reduces the positive effect of size on performance. Finally, diversification by the layer of the structure also affects performance at the group level, when diversification is concentrated closer to the holding company the effect on performance at the group level tends to be positive, otherwise negative.